Methane emissions in selected hard-coal mines of the Upper Silesian Coal Basin in 1997–2016 - Dreger, Marcin (Geology, Geophysics and Environment, 2019)
Hard coal is extracted in the Upper Silesian Coal Basin (USCB) from deeper and deeper coal seams every year. In 2000, the average depth of coal extraction was 600 m, in 2010 – 700 m, but in the last two years (2016–2017) this has been extended to a depth of 770 m. The USCB is not homogeneous in layout in terms of methane hazard, but rather very diverse. Therefore, the USCB has been divided into seven gassy regions to show differences in methane danger distribution.Northern and central USCB regions (I, II and III) are the mostly naturally degassed, so the most dangerous gassy conditions are in the IV and V regions, where methane content in coal seams varies from 6 m3/Mg coaldaf to above 18 m3/Mg coaldaf. The two westernmost USCB gassy regions (VI and VII) are poorer in methane than the IV and V areas.Six representative coal mines were chosen: Mysłowice-Wesoła, Budryk, Brzeszcze, Pniówek, Marcel and Rydułtowy-Anna based on their high hard coal production and total methane emissions. The reason for the highest methane emission in those regions might be fault tectonics facilitating methane migration and also the thick and continuous Miocene cover constituting a hermetic screen for gases in the southern part of the USCB.